Pengaruh Financial Distress, Firm Life Cycle, dan Corporate Restructuring Terhadap Nilai Perusahaan: Studi Empiris Perusahaan Infrastuktur yang Terdaftar di BEI Tahun 2020-2022 - Sayyidah Alifah Rahmani; Erma Setiawati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to determine the effect of financial distress, firm life cycle, and corporate restructuring on firm value in infrastructure sector companies for the period 2020-2022. This type of research is a quantitative study that uses secondary data, namely audited financial reports and is presented in the Company's annual report. The sampling technique in this study used purposive sampling technique with a total sample of 105 data during the 2020-2022 period. The analysis used in this research is multiple linear regression analysis. The results of this study indicate that firm life cycle has an effect on firm value. while financial distress and corporate restructuring have no effect on firm value.